Match performance indicators that discriminated between winning, drawing and losing teams in the 2017 AFCON soccer championship - Kubayi, A.; Toriola, A. (Journal of Human Kinetics, 2020)
The purpose of this study was to examine match performance indicators that discriminated between winning, drawing and losing teams in the 2017 Total Africa Cup of Nations (AFCON) soccer championship. Data were collected from 32 matches during the AFCON soccer tournament using the InStat® system. The studied variables included the number of goals scored, the time period in which a goal was scored and the impact of the first goal on the match outcome, as well as total shots, shots on goal, total passes, accurate passes, corners, ball possession, fouls, offsides as well as yellow and red cards. The results showed that goals scored (1.80 ± 0.83), total shots (11.05 ± 4.83), shots on target (4.70 ± 2.62), fouls (18.60 ± 5.19), offsides (2.35 ± 1.76), yellow cards (1.55 ± 1.10), and red cards (0.05 ± 0.22) were discriminative performance indicators of winning teams. In contrast, losing teams yielded higher mean values in total passes (260.30 ± 49.10), accurate passes (69.28 ± 5.74), corners (5.10 ± 2.95), and ball possession (51.20 ± 5.52). In conclusion, these results have practical implications for coaches in planning and implementing team tactics for successful performance.